Childbirth experience and practice changing during COVID‐19 pandemic: A cross‐sectional study. Issue 6 (18th May 2021) - Inversetti, Annalisa; Fumagalli, Simona; Nespoli, Antonella; Antolini, Laura; Mussi, Serena; Ferrari, Debora; Locatelli, Anna
Abstract: Aim: To evaluate mothers' satisfaction with childbirth experience in a cohort of women who delivered during COVID pandemia and to compare them to a pre‐COVID cohort. Design: We performed a cross‐sectional study in a low‐risk Maternity Unit. Methods: Women who delivered during COVID‐19 pandemic were compared to a pre‐COVID cohort recruited in 2018 in the same setting. Italian version of the Birth Satisfaction Scale‐Revised (I‐BSS‐R) was used. Results: Three hundred and seventy‐seven women were included (277 pre‐COVID and 100 during COVID pandemic). No differences in terms of satisfaction at birth were reported (I‐BSS‐R mean 27.0, SD 5.3 versus mean 27.6, SD 6.1, p 0.34), despite an increased rate of active intrapartum interventions. Intrapartum variables that significantly reduced satisfaction were the same in the two groups: epidural analgesia ( p < .0001 in both groups), prolonged active phases ( p < .0001 in both), oxytocin administration ( p < .0001 in both) and operative delivery (p 0.0009 versus p 0.0019).